Integrasi Human Resource (HR) Analytics sebagai Strategi dalam Meningkatkan Pengalaman Karyawan - Azmil Indillah Suwandi; Imariana Nur Mutiara; Qoonita Nurhasanah; Afrian Bintang Putra; Mada Aditia Wardhana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the integration of Human Resource (HR) Analytics as a strategic approach to enhancing employee experience in organizational settings. The growing complexity of the business environment and the increasing demand for data-driven decision-making have encouraged organizations to utilize HR Analytics in managing human resources more effectively. This research employs an integrative literature review method to synthesize findings from previous empirical and conceptual studies published between 2014 and 2024. The review process was conducted systematically through article identification, selection, thematic analysis, and synthesis of findings. The results indicate that HR Analytics contributes positively to employee experience by improving employee engagement, performance management, and retention strategies. Furthermore, organizational culture, leadership commitment, and technological readiness are identified as key moderating factors influencing the successful implementation of HR Analytics. This study provides theoretical contributions by strengthening the conceptual relationship between HR Analytics and employee experience, as well as practical implications for organizations seeking to design data-driven human resource management strategies.